Marijuana : uses, effects and the law - Rojas, Andrea S. (Substance abuse assessment, interventions and treatment series., 2011)
The cannabis sativa plant, more commonly known as marijuana, has been used medicinally for millenia and continues to play a significant role in medical treatment today. This book presents topical research in the study of marijuana; its uses, effects and legal issues. Topics discussed include measurement of cannabis consumption to assess the role of drug potency in rising rates of cannabis misuse disorders; the influence of marijuana legislation on vulnerable populations; marijuana use among adolescents and its effects and recreational marijuana use in a bariatric clinic population. --